Cutaneous-ganglionar rickettsiosis by Rickettsia conorii in Uruguay - Conti-Diaz, Ismael A.; Rubio, Ivonne; Somma Moreira, Raúl E.; Pérez Bórmida, Graciela (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
Three autochthonous cases of cutaneous-ganglionar rickettsiosis transmitted by dogs ticks (Amblyomma maculatum in one of them) are reported. Two of the three cases were undoubtely produced by Rickettsia conorii according to the results of the specific indirect immunofluorescence technique IEF-IgM anti R. conorii. A third case is included due to the clinical epidemiological similarity, the positive serum reactivity with Proteus O x 19 and the rapid response to tetracycline. Autochthonous rickettsiosis by R. conorii has not been previously registered in the American area what confers special interest to this communication. The search of the disease in the other countries of the region is suggested.